Macroeconomic policy evaluation in an SFC econometric model: the case of the investment programme for climate action in France - Chin Yuan Chong; Jacques Mazier; Luis Reyes (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
We study the macroeconomic impact of climate action policy that would allow France to reach its net zero objective by 2050. This policy, detailed in a report commissioned by the French Prime Minister, requires significant additional investments to be made by firms, households and the public sector. Contrary to the findings of the report, our simulations show that these investments are likely to generate economic growth and reduce public debt. However, since growth increases import demand, the trade balance and foreign debt worsen significantly, showing that the foreign sector benefits from France undertaking climate finance domestically. Unfortunately, the cost of climate action is borne mainly by firms and households whose financial position worsens considerably. Our tool for the analysis is a medium-scale empirical stock-flow consistent model built for the French economy (SFC FR).
Keywords: E12; E62; 330; climate investments; climate transition policy; empirical SFC models